2021
DOI: 10.1093/tropej/fmab025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Characteristics of Paediatric Patients Diagnosed with COVID-19 in a Tertiary Hospital in Mexico City

Abstract: COVID-19 affects the paediatric population less frequently than adults. A retrospective study was performed in a tertiary paediatric hospital in Mexico City in children <18 years of age who were hospitalized with a positive reverse transcription-polymerase chain reaction for SARS-CoV-2. Included in the study were 86 patients with a median age of 10 years old (IQR 2.6–14.3 years), who were classified in three groups: previously healthy, with chronic disease and immunosuppressed patients. The principal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
2
14
2
Order By: Relevance
“…On the other hand, one large series from the US reported that 29.6% of the hospitalized COVID‐19 infections required intensive care unit admission, 17 while different studies from Mexico City and the USA reported that 23.0% and 39% of the children required PICU admission. 18 , 19 In our study, we didn't observe any significant difference regarding pediatric intensive care unit admission for both of the viral infections. Moreover, admission to the intensive care unit was associated with an underlying disease regardless of the type of pandemic.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, one large series from the US reported that 29.6% of the hospitalized COVID‐19 infections required intensive care unit admission, 17 while different studies from Mexico City and the USA reported that 23.0% and 39% of the children required PICU admission. 18 , 19 In our study, we didn't observe any significant difference regarding pediatric intensive care unit admission for both of the viral infections. Moreover, admission to the intensive care unit was associated with an underlying disease regardless of the type of pandemic.…”
Section: Discussioncontrasting
confidence: 57%
“…There are very few reports on the Mexican pediatric population hospitalized with SARS-CoV-2 and, in the case of Mexico City, the clinical and epidemiological profile of this population is even less well characterized. Macias-Parra and colleagues studied a cohort ( n = 86) of pediatric patients hospitalized with SARS-CoV-2 infection at a tertiary hospital in Mexico City, finding that 40% of the patients were >12 years old, 21% manifested severe and critical disease, and the mortality of the cohort was 5% [ 12 ]. Oliver-López and colleagues studied a cohort ( n = 510) from a pediatric referral hospital in Mexico City, including inpatients and outpatients that met the criteria for a suspected case by the Mexican Epidemiological Surveillance Directorate [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This clinical scenario has been observed in Mexican children and reported by the group of the National Institute of Paediatrics. [35] In this report, 62% of the studied population did not report previous diseases and it is conceivable that a fraction of this population had presented with this multisystem inflammatory syndrome, however, we recognize that we cannot affirm that this would have been the diagnosis. Therefore, more research is required to ascertain if this condition exists in the Mexican population.…”
Section: Discussionmentioning
confidence: 72%